Robot Pengiriman Obat Dengan Rute Tercepat Menggunakan Algoritma Djikstra - Ilham Bagastama (Universitas Islam Balitar Blitar, 2022)
ABSTRACT The development of today's era has become a necessity where technology is one of the important factors in human life, humans always create innovations to make work easier and solve problems that always arise. In December 2019 the emergence of a pandemic caused by a virus called Covid -19 This virus can be transmitted from human to human through splashes of body fluids or contaminated surfaces. To solve this problem the author took the initiative to help nurses by designing drug distribution tools so that nurses do not need to make direct contact with patients and drug distribution will be sent more efficiently, this tool uses a TCRT line sensor which is used to identify the path then the data is sent to the Arduino microcontroller UNO to be processed to find out the fastest route using the djikstra algorithm then instructs the DC motor to move towards the cooled destination.